Perlindungan Hak Cipta Terhadap Pencipta Lagu yang Diunggah Ulang Melalui Aplikasi Tiktok - Az Zahra, Shabrina Najla; Fauziyyah, Laila (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Song duplication by TikTok users on social media TikTok often occurs without their knowledge and may be illegal. This article looks at the legal disputes that occur between TikTok users and the owners of the copyrights of music that are posted and shared on the social media platform. A normative legal method based on relevant laws is used in this research. The findings of the study demonstrate that the music included on TikTok are legally protected by copyright, in compliance with Law Number 28 of 2014 respecting Copyright, meaning that infringers may face penalties in line with relevant laws. In order to react to copyright violations in its application, TikTok has also worked with music owners via licensing arrangements, wherein content consumers serve as third parties and use the licensing agreement. Therefore, in order to prevent legal infractions that might endanger copyright holders, TikTok users are urged to comprehend and respect copyright more.